2011
DOI: 10.1590/s0104-42302011000400015
|View full text |Cite
|
Sign up to set email alerts
|

Use of a lactic acid plus lactoserum intimate liquid soap for external hygiene in the prevention of bacterial vaginosis recurrence after metronidazole oral treatment

Abstract: A lactic acid plus lactoserum liquid soap for external intimate hygiene may be an option for the prevention of BV recurrence after treatment and cure with oral metronidazole.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0
3

Year Published

2012
2012
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(16 citation statements)
references
References 20 publications
0
13
0
3
Order By: Relevance
“…65 Other unblinded studies have reported that lactate gel inserted into the vagina for 7 days is as effective as oral metronidazole in the treatment of BV 66 and that topical use of lactic acid and lactoserum intimate liquid soap following standard oral metronidazole treatment reduced BV recurrence. 67 Further blinded controlled studies are warranted to examine the potential for l -lactic acid, particularly applied continuously via an intravaginal ring, for BV treatment and prevention.…”
Section: Discussionmentioning
confidence: 99%
“…65 Other unblinded studies have reported that lactate gel inserted into the vagina for 7 days is as effective as oral metronidazole in the treatment of BV 66 and that topical use of lactic acid and lactoserum intimate liquid soap following standard oral metronidazole treatment reduced BV recurrence. 67 Further blinded controlled studies are warranted to examine the potential for l -lactic acid, particularly applied continuously via an intravaginal ring, for BV treatment and prevention.…”
Section: Discussionmentioning
confidence: 99%
“…However, the results concerning this strategy are controversial since acidification strategies alone, using acetic acid (Holley et al, 2004 ) or acid-buffering formulation (Simoes et al, 2006 ) showed to be somewhat ineffective against BV. Recently, Bahamondes and colleagues verified that a soap containing lactic acid and lactoserum could be used for external intimate hygiene, reducing BV recurrence after treatment with oral metronidazole (Bahamondes et al, 2011 ). Interestingly, vitamin C, when coated with silicon, allowed the constant release of the active agent, resulting in a long-lasting vaginal low pH and prevention of vaginal irritation (Polatti et al, 2006 ).…”
Section: Emerging Therapeutic Alternatives Against Bvmentioning
confidence: 99%
“…Vaginal lactic acid is important, as it correlates with vaginal health by inhibiting the growth of bacteria known to cause vulvovaginal infections [20] and may also play a part in local immune defense [24]. External feminine washes, particularly those containing lactic acid and formulated to an acidic pH that enhances skin homeostasis, are considered more appropriate than internal washes or douches and may be a useful adjunct therapy for women with vaginal infections or taking antibiotics [21].…”
Section: Discussionmentioning
confidence: 99%
“…A novel gel wash formulation containing lactic acid (pH 4.2) intended for daily external use was formulated to provide gentle cleansing, freshness, and antimicrobial protection to help maintain a healthy balance of the intimate skin area for women. The gel wash contains 2% lactic acid, a key natural antimicrobial ingredient that correlates with vulvovaginal health, as lactic acid helps maintain an acidic pH in the vulvovaginal area to augment skin homeostasis and prevent the growth of harmful bacteria [20][21][22]. The formulation was tested in vitro following standardized ASTM (American Society for Testing and Materials) test methodology (ASTM E2315-03 Standard Guide for Assessment of Antimicrobial Activity Using a Time-Kill Procedure) and demonstrated effective antimicrobial activity (minimum of 1 log kill) against fungi (Candida albicans), Gram-positive (including activity against Group B Streptococcus and Staphylococcus aureus) and Gram-negative bacteria (including Escherichia coli; data not shown).…”
Section: Introductionmentioning
confidence: 99%